智媒时代下高校辅导员开展心理健康教育的优化路径研究 - 雷兴强 (现代高等教育研究, 2026)
In the era of intelligent media, university counselors’ engagement in mental health education is not only a practical necessity to adapt to media transformations and safeguard students’ psychological well-being, but also a crucial approach to meeting contemporary demands and innovating pathways for psychological education. However, counselors currently face practical dilemmas in this environment, including cognitive lag, competency deficits, and rigid working mechanisms. In response, this paper proposes optimization pathways from three dimensions: updating educational philosophies, enhancing professional competencies, and innovating institutional mechanisms. These measures aim to promote the deep integration of psychological education with intelligent media technologies, thereby improving the overall effectiveness of mental health education in universities.